Taking Sides : Clashing views on Controversial Issues in Teaching and Educational Practice - Evans, Dennis (Dubuque, IA : McGraw-Hill/Dushkin, 2005)
Presents debate-style essays on twenty educational issues including grading, discipline programs, abstinence-only programs, school uniforms, American history, and achievement-level tracking
Is homework harmful to students? -- Does the practice of grading students serve useful purposes? -- Do classroom "discipline programs" contribute to ethical behavior? -- Are "abstinence only" programs the best approach to sex education instruction? -- Is "whole language" a legitimate approach to literacy education? -- Can Web-based learning transform the classroom? -- Is the traditional approach to American history too exclusionary? -- Should the study of literature focus on the classics? -- Are single-sex classrooms better for students? -- Should classroom instruction focus on preparation for the workplace? -- Should all students follow a common curriculum? -- Is achievement level tracking of students a defensible practice? -- Is block scheduling better than traditional scheduling? -- Is grade inflation a problem? -- Are school uniforms beneficial? -- Is drug testing of students a justifiable practice? -- Should religious content and concepts be more evident in our schools? -- Should teacher pay be tied to student performance? -- Should service learning be required? -- Is home schooling a good idea?
Includes bibliographical references and index
Keywords: Education, Secondary -- United States